Measuring the dark side (with weak lensing) - Amendola, Luca; Kunz, Martin; Sapone, Domenico (Arxiv, 2007)
We introduce a convenient parametrization of dark energy models that is general enough to include several modified gravity models and generalized forms of dark energy. In particular we take into account the linear perturbation growth factor, the anisotropic stress and the modified Poisson equation. We discuss the sensitivity of large scale weak lensing surveys like the proposed DUNE satellite to these parameters. We find that a large-scale weak-lensing tomographic survey is able to easily distinguish the Dvali-Gabadadze-Porrati model from LCDM and to determine the perturbation growth index to an absolute error of 0.02-0.03.